2020
DOI: 10.1891/jdnp-d-19-00054
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Transformational Leadership Education Session for Nurse Leaders and Nurse Educators

Abstract: BackgroundTransformational leadership is one of the most utilized models of leadership across the disciplines. It can positively impact the leader-follower relationship, performance of the leader, and productivity of the organization.ObjectiveThe purpose of the project was to assess the impact of an educational session on the recognition and execution of transformational leadership characteristics for nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Along with the present study, Singh (2020) (40) demonstrated statistically significant increase of transformational leadership dimensions after educational sessions about the transformational leadership. Mallek and El-Hosany (2020) (33) found that majority of clinical instructors' level of knowledge in post intervention were excellent.…”
Section: Ii) Immediate Post Educational Programsupporting
confidence: 82%
“…Along with the present study, Singh (2020) (40) demonstrated statistically significant increase of transformational leadership dimensions after educational sessions about the transformational leadership. Mallek and El-Hosany (2020) (33) found that majority of clinical instructors' level of knowledge in post intervention were excellent.…”
Section: Ii) Immediate Post Educational Programsupporting
confidence: 82%
“…This result revealed the important role of TL in explaining the interaction between WFC and patient safety outcomes. This could be because relational leadership styles, including TL, enable an empowering work environment in which staff nurses are provided greater discretion over their job and more professional authority over their nursing practice, allowing them to achieve work–family balance, ultimately improving patient outcomes (Ree, 2020; Singh, 2020). Further, a leader demonstrating TL encourages decision‐making and problem‐solving skills, which are known to have a positive influence on the individual's ability to reconcile family and job demands, which subsequently leads to better nursing care provision and fewer patient safety concerns (Boamah et al, 2018; Weeks et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TL in nurses can be fostered by employing leadership development training (e.g. leadership simulation, leadership education, encouraging nurse managers to take relevant certifications and further education; Singh, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Certain professions, such as social workers and nurses, have different functions in different countries. The development of advanced practices would make it possible to acquire skills in case management (and, thus, patient data management) or team leadership (Goldsberry, 2018;Singh, 2020).…”
Section: Perspectivesmentioning
confidence: 99%